Analysis of Multicultural Counseling and Social Justice Competencies Framework amid Cultural Diversity for Counselor Professionalism in Indonesia - Moch. Syihabudin Nuha; Muhammad Ali Najich; Miftahul Jannah; Moch. Syihabudin Nuha; Muhammad Ali Najich; Miftahul Jannah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The increasing cultural diversity in social life necessitates that counselors possess adequate multicultural competencies to effectively serve clients from various backgrounds. Considering a client's cultural context is essential to prevent bias and stereotypes, thereby enhancing counselor professionalism when addressing the diversity inherent in each student. This study aims to explore and analyze the importance of multicultural counseling competencies for counselors by reviewing existing literature. The primary objective is to synthesize findings from previous research to highlight key competency frameworks relevant to contemporary practice. This research employs a Systematic Literature Review (SLR) method. The study analyzed 30 journal articles, consisting of 14 international and 16 national journals from the 2013-2023 period. Literature was obtained through a systematic Google Scholar search using the keyword "Multicultural Counseling Competence." Data analysis involved qualitative synthesis of findings from selected articles. The findings consistently emphasize the critical importance of Multicultural Counseling Competencies (MCC) and the Multicultural and Social Justice Counseling Competencies (MSJCC). These frameworks are identified as essential, comprehensive packages of multicultural competencies that professional counselors need to work effectively in diverse settings. This study confirms that MCC and MSJCC are fundamental to ethical and effective counseling practice in multicultural contexts. The results serve as a crucial reference for policymakers to formulate evidence-based policies addressing students' needs from diverse backgrounds. Furthermore, the findings provide a valuable foundation for designing counselor training programs, particularly in culturally rich nations like Indonesia, to strengthen professional competence in multicultural counseling.